PENGETAHUAN PESERTA DIDIK DI KOTA PONTIANAK TERHADAP PERMAINAN RAKYAT DAN OLAHRAGA TRADISIONAL - Andika Triansyah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The industrial revolution 4.0 brought digitalization to human life so that people's games and traditional sports which were full of meaning were neglected and began to be drowned out by the rise of instant, high-tech games that tended to lead to immobilization. Paying attention to this, efforts are needed to examine the existence of folk games and traditional sports in the midst of society, especially among students. The research method used is descriptive quantitative in the form of a survey. The subjects in the study were students in the city of Pontianak totaling 311 students. With a distribution of 118 students in elementary schools, 91 students in junior high schools, and 102 students in senior high schools. The results of the study showed that there were 12 games known to students in Pontianak City. The intensity of students playing traditional games in the frequent category is 37% and the rare and very rare categories are at 63%. Furthermore, students most often play traditional games during holidays, namely by 58%, and play traditional games at school by 23% and are played in the afternoon and evening by 19%. There are 7 obstacles in playing, the biggest obstacle is the absence of friends to play with 67%, no game tools 47%, fear of injury 21%, not knowing how to play 16%, frequent fights 10%, forbidden by parents 5%, and unpleasant 4 %.